2018
DOI: 10.1038/s41419-018-0446-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive effect of arsenic trioxide on islet xenotransplantation prolongs xenograft survival in mice

Abstract: The role of arsenic trioxide (As2O3) in inhibiting immune rejection and prolonging islet allograft survival has been identified in islet allotransplantation. This study aims to explore the role of As2O3 in islet xenotransplantation and the action mechanism. The streptozotocin (STZ) was used in C57BL/6 mice to induce the type 1 diabetes mellitus (T1DM) for xenotransplantation models establishment. Donor islets were isolated by digesting. The flow cytometry (FCM) was used to analyze lymphocyte types. The blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
7
3
0
Order By: Relevance
“…The development of tolerance to grafts is associated with the levels of CD4 + Foxp3 + Tregs 34 and Th1/Th2 balance 35 . In our study, flow cytometric analysis showed no significant change in CD4 + Foxp3 + Tregs in recipient spleen after LEF therapy (data not shown), which was consistent with the reports that LEF cannot induce CD4 + Foxp3 + Treg generation 15 , 16 in xenotransplantation. In addition, the influence of LEF on Th1 (IFN-γ) and Th2 cells (IL-4) was determined in xenografts.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The development of tolerance to grafts is associated with the levels of CD4 + Foxp3 + Tregs 34 and Th1/Th2 balance 35 . In our study, flow cytometric analysis showed no significant change in CD4 + Foxp3 + Tregs in recipient spleen after LEF therapy (data not shown), which was consistent with the reports that LEF cannot induce CD4 + Foxp3 + Treg generation 15 , 16 in xenotransplantation. In addition, the influence of LEF on Th1 (IFN-γ) and Th2 cells (IL-4) was determined in xenografts.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, LEF has the potential to inhibit both T and B cell functions. However, in vivo experiments have demonstrated the opposite results 15 . In a mouse-to-rat heart transplantation model 16 , LEF monotherapy showed no effect on the production of Th1 cytokines and T cell function.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al reported ATO has the immunosuppressive effect of arsenic trioxide on islet xenotransplantation and they found ATO inhibited proliferation of T lymphocyte and increased the proportion of Foxp3 + regulatory T cells in recipient mice [43]. Based on our results, we suggest ATO induced upregulation of PD-L1, which negatively regulates T cell immunity, is probably one of the underlying molecular mechanisms of the immune suppressive effects of ATO observed in the mouse islet xenotransplantation model.…”
Section: Discussionsupporting
confidence: 72%
“…In the treatment of APL, ATO has a specific pro-apoptotic effect on leukaemic cells and decreases the amount and inhibits the function of Treg cells [ 34 ]. However, in a murine islet allotransplantation model, ATO inhibited immune rejection and prolonged islet allograft survival by increasing the proportion of Foxp3+ Treg cells, inhibiting proliferation of T lymphocytes and decreasing B lymphocytes [ 35 ]. ATO, when combined with co-stimulation blockade, prolongs the survival of cardiac allografts in alloantigen-primed mice.…”
Section: Discussionmentioning
confidence: 99%